The higher spin Laplace operator in several vector variables. (15th January 2018) - Eelbode, David; Raeymaekers, Tim; Roels, Matthias
Abstract: In this paper, an explicit expression is obtained for the conformally invariant higher spin Laplace operator, which acts on functions taking values in an arbitrary (finite-dimensional) irreducible representation for the orthogonal group with integer valued highest weight. Once an explicit expression is obtained, a special kind of (polynomial) solutions of this operator is determined.